Transformasi Ekonomi Digital Indonesia Dalam Mewujudkan Indonesia Emas 2045: Pemikiran Prof. Nurcholish Madjid - Ramadhan, Fardhal Virgiawan (ITB AAS INDONESIA Surakarta, 2024)
Digital economic transformation is one of the agendas in the 2025-2045 National Long-Term Development Plan (RPJPN) or what is known as Golden Indonesia 2045. In an effort to realize a Golden Indonesia 2045, Indonesia must create smart leadership by implementing Islam, Indonesianism, and Modernity as planned by Nurcholish Madjid. The aim of this research is to explain and analyze the digital economic transformation in smart leadership to realize Golden Indonesia 2045 in Nurcholish Madjid's thinking. The research method used is a qualitative method with an analytical-descriptive research type. The results of this research are that the digital economic transformation carried out by Indonesia is a form of modernization, not a form of Westernization, but rather an openness in applying positive values for world progress in accordance with Nurcholish Madjid's thoughts. Islam, Indonesianness, and Modernity proclaimed by Nurcholish Madjid is proof that the digital economic transformation is a form of rationalization regarding Islamic principles and teachings that are open to reason and science. This is in accordance with smart leadership which includes social leaders, digital leaders, freshmen leaders, and technological leaders, that Nurcholish Madjid is open to the values of universality and knowledge. In digital economic transformation too, Nurcholish Madjid said that the Muslim Society must be optimistic and open to becoming a Modern Moslem Society to realize a Golden Indonesia 2045.